Mechanical and microstructural investigations of tungsten and doped tungsten materials produced via powder injection molding. (July 2015) - Antusch, Steffen; Armstrong, David E.J.; Britton, T. Ben; Commin, Lorelei; Gibson, James S.K.-L.; Greuner, Henri; Hoffmann, Jan; Knabl, Wolfram; Pintsuk, Gerald; Rieth, Michael; Roberts, Steve G.; Weingaertner, Tobias
Highlights: Mass production of near-net-shape parts. Brittle to ductil transition for pure PIM W at 400°C (low strain rates). No porosities or cracks, high density (better than 99 % T.D.). No recrystallisation – possible grain growth at very high temperatures only. Fully anisotropic material properties. High thermal shock resistance. Abstract: The physical properties of tungsten such as the high melting point of 3420°C, the high strength and thermal conductivity, the low thermal expansion and low erosion rate make this material attractive as a plasma facing material. However, the manufacturing of such tungsten parts by mechanical machining such as milling and turning is extremely costly and time intensive because this material is very hard and brittle. Powder Injection Molding (PIM) as special process allows the mass production of components, the joining of different materials without brazing and the creation of composite and prototype materials, and is an ideal tool for scientific investigations. This contribution describes the characterization and analyses of prototype materials produced via PIM. The investigation of the pure tungsten and oxide or carbide doped tungsten materials comprises the microstructure examination, element allocation, texture analyses, and mechanical testing via four-point bend (4-PB). Furthermore, the different materials were characterized by high heat flux (HHF) tests applying transient thermal loads at different base temperatures to address thermal shock and thermal fatigue performance. Additionally, HHF investigations provide information about the thermo-mechanical behavior to extreme steady state thermal loading and measurements of the thermal conductivity as well as oxidation tests were done. Post mortem analyses are performed quantifying and qualifying the occurring damage with respect to reference tungsten grades by metallographic and microscopical means.